Metode Pendidikan Akhlak Dalam Kitab Adab Al-Mufrad Karya Imam Bukhari (Tahun 194-256 H). - Hery Kiswanto (AL-QOLAM : Jurnal Dakwah dan Pemberdayaan Masyarakat, 2021)
Morals education becomes a prominent pillar in establishing Islamic society. This research was intended to investigate the educational methods used by Prophet in educating morals of his friends explained in Adab al-Mufrad Book. This book was written exclusively by Imam Bukhari to examine specifically about Hadiths related to morals and characters. The purposes of this research were to identify and analyze the moral educational methods in Adab al-Mufrad by Imam Bukhari. This research was qualitative research. This research used library research. In the research implementation, the researcher collected qualitative data to be described and analyzed in the form of explorative research which had the purposes to receive information, insights, knowledge, idea, and comprehension as the effort to formulate and define the problems. The data analysis used in this research was descriptive analysis. The descriptive analysis data was frequently analyzed based on the content, and often called as content analysis. The findings of this research demonstrated that 1332 hadiths in Adab al-Mufrad by Imam Bukhari showed the morals educational method was used by Prophet to educate his friends. The details of the findings were 110 hadiths for Hiwar method, 21 hadiths for narrative method, 27 hadiths for amtsal method, 207 hadiths for qudwah method, 203 hadiths for ‘ibrah wa mauizah method, 184 hadiths for mumarasah wal amal, 119 hadiths for targhib method, and 107 hadiths for tarhib method. The results of the work indicates that according to Adab al-Mufrad there are two main superiorities of educator; first, a good deed and second, the most giving-benefit man to other. Keywords: Method, Moral Education, Adab al-Mufrad Book